ANALISIS SEMIOTIKA ROLAND BARTHES: FILM ANIMASI SPIRITED AWAY DALAM REPRESENTASI NILAI MORAL - Siswanta, Yusuf Alfandi, Dian Esti Nurati & (Transformasi, 2017)
The movie has a messange about a girl chld who is able to save both parents when they lack,The main character is Chihiro. This study aims to describe how obedience to parents ofchildren in the film spirited away. The methodology used in this study is semiotics rolandbarthes by analyzing through the symbol of symbols and myths based on research results. Itcan be seen the value of obedience to parents of children in the film spirited away through thethree categories: Willing to sacrifice. Devotion. Affection. Struggel and self-sacrifice of a childto save her parents in order to be delivered from the curse of the witch yubaba. That created amovie similar to impart knowledge to the theory semioticKey words: willing to sacrifice, dedication, affection